The growth responses of orchid, Phalaenopsis hybrid to the inoculation of Rhizoctonia solani - Norhayati Yusuf,; Nurul Aliaa Idris,; Zalifah Katman, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The orchid mycorrhizal association is a symbiotic interaction in which both plants and fungi are mutually beneficial. Mycorrhizal association increases plant access to soil nutrients and is especially important for orchid seed germination. Most orchid mycorrhizal fungi belong to the group Rhizoctonia, including Rhizoctonia solani, a well-known plant pathogen that affects major crop production worldwide but has also been reported to be an orchid mycorrhiza. However, no systematic study has been done to investigate the type of interaction that develops when pathogenic R. solani interact with an orchid; whether a pathogen can alter its association to become mycorrhizal. Thus, this study was conducted to determine the type of interaction between Phalaenopsis hybrid and R. solani and its effect on the growth and chlorophyll content of Phalaenopsis hybrid. Sterile ex vitro Phalaenopsis plantlets were inoculated with 4 discs (0.5 cm diameter) of R. solani, isolated from diseased rice tissues, and incubated for 9 days. The inoculated root segments were used to observe the fungal hyphae in the root cell. The growth parameters (plant height, leaves length and width, the number of leaves, fresh and dry weights) and chlorophyll content were determined at 0, 3, 6, 7, 8, and 9 days of inoculation. It was observed that no peloton was present in the root cells of all inoculated plants. Severe reduction of growth and chlorophyll content were obtained in inoculated plants compared to control especially after 7 days of inoculation. These results suggested that R. solani developed a pathogenic infection to Phalaenopsis hybrid as no peloton structure was present in the root cells. R. solani infection also reduces the Phalaenopsis hybrids growth as well as declined its chlorophyll content.